2019
DOI: 10.1097/cm9.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association of appropriateness of coronary revascularization and 1-year clinical outcomes for patients with stable coronary artery disease in China

Abstract: Background: The Chinese appropriate use criteria (AUC) for coronary revascularization was released in 2016 to improve the use of coronary revascularization. This study aimed to evaluate the association between the appropriateness of coronary revascularization based on the Chinese AUC and 1-year outcomes in stable coronary artery disease (CAD) patients. Methods : We conducted a prospective, multi-center cohort study of stable CAD patients with coronary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 22 publications
0
21
0
3
Order By: Relevance
“…10 Prior data showed that 18.1% of the overall decision-making for patients with stable angina was classified as inappropriate based on a single disciplinary decision, especially among patients undergoing PCI. 32 The heart team, a medium of communication to integrate the input of numerous specialists, can help to minimise fragmented communication between specialists and eliminate specialist bias in the decision-making process. It was reported that heart team recommendations differed from those of the original treating interventional cardiologist in approximately one-third of cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Prior data showed that 18.1% of the overall decision-making for patients with stable angina was classified as inappropriate based on a single disciplinary decision, especially among patients undergoing PCI. 32 The heart team, a medium of communication to integrate the input of numerous specialists, can help to minimise fragmented communication between specialists and eliminate specialist bias in the decision-making process. It was reported that heart team recommendations differed from those of the original treating interventional cardiologist in approximately one-third of cases.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, appropriate revascularisation is associated with improved 1-year outcomes in patients with appropriate indications and has no benefit in those with uncertain or inappropriate indications. 19 Thus, we assume that revascularisation recommendations of dedicated heart teams organised by the standardised heart team protocol would be more stable and appropriate compared with those of general heart teams based on guideline principles, which leads to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations